2018
DOI: 10.1136/rmdopen-2018-000673
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic course of early undifferentiated arthritis under treatment is not dependent on the number of joints with erosions at diagnosis: results from the Swiss prospective observational cohort

Abstract: ObjectiveTo analyse whether early arthritis patients who do not fulfil the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) 2010 classification criteria for rheumatoid arthritis (RA) have a different course of the disease dependent on whether they can or cannot be classified as RA because of radiographic disease (EULAR task force) at diagnosis.MethodsFor this observational study within the Swiss RA cohort SCQM, we included patients with early undifferentiated arthritis (disease d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“… 20 However, a recently published study has shown that the clinical and radiographic course in ACR/EULAR 2010 negative patients under treatment was not dependent on the presence of erosions at diagnosis. 21 …”
Section: Discussionmentioning
confidence: 99%
“… 20 However, a recently published study has shown that the clinical and radiographic course in ACR/EULAR 2010 negative patients under treatment was not dependent on the presence of erosions at diagnosis. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, se identificaron pacientes que progresaron a otras artropatías, en su mayoría a AR, lo que es similar a otras cohortes (19)(20)(21) reportadas en la literatura y sin diferencias significativas a lo reportado a nivel local (13).…”
Section: Discussionunclassified
“…Se encontró que la mayoría de los pacientes eran de sexo femenino y fueron diagnosticados en un rango de edad entre los 45 y 50 años, similar a lo reportado en otras series previamente publicadas (21).…”
Section: Discussionunclassified
“…While early signs and symptoms of RA can be mimicked by other diseases, there are some which should be taken into consideration, such as fatigue, minimal joint pain, joint warmth, joint stiffness, limping, reduction of range of motion, fever, anemia, and depression. It is easy to see that all these are not at all specific, not even for full blown rheumatoid arthritis and even less so for early/very eRA [35].…”
Section: Clinical Picture Of Early Arthritismentioning
confidence: 99%
“…This symptom can affect relationships, emotions, mood, productivity, creativity, the general feeling of happiness. Fatigue from RA can associate with poor appetite and weight loss [35].…”
Section: Clinical Picture Of Early Arthritismentioning
confidence: 99%